2015
DOI: 10.1371/journal.pone.0122579
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cytotoxicity of Carbon-Based Nanoparticles, Diamond and Graphite, in Human Glioblastoma and Hepatoma Cell Lines

Abstract: Nanoparticles have attracted a great deal of attention as carriers for drug delivery to cancer cells. However, reports on their potential cytotoxicity raise questions of their safety and this matter needs attentive consideration. In this paper, for the first time, the cytotoxic effects of two carbon based nanoparticles, diamond and graphite, on glioblastoma and hepatoma cells were compared. First, we confirmed previous results that diamond nanoparticles are practically nontoxic. Second, graphite nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 48 publications
3
42
0
Order By: Relevance
“…33 Similarly, ND and NG show low toxicity on glioblastoma and hepatocellular carcinoma cells. 34 Moreover, ND has been suggested to be biocompatible with neuroblastoma cells and macrophages. 35 However, neuroblastoma cells lose their neurite extensions after incubation with ND at a concentration of 100 μg/mL, and macrophages show morphological changes at this dose.…”
Section: Resultsmentioning
confidence: 99%
“…33 Similarly, ND and NG show low toxicity on glioblastoma and hepatocellular carcinoma cells. 34 Moreover, ND has been suggested to be biocompatible with neuroblastoma cells and macrophages. 35 However, neuroblastoma cells lose their neurite extensions after incubation with ND at a concentration of 100 μg/mL, and macrophages show morphological changes at this dose.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of the phospholipid bilayer following GO treatment has already been documented in Hep G2 cells, although authors could not conclude whether or not the damage depended on the orientation of the nanoparticles [18]. Entrance of nanoparticles into cells, apart from phagocytes, has been a concern for many researchers, as most studies on cytotoxicity of nano-diamonds, for example, have not been able to decide if particles were inside cells or aggregated on plasmamembranes [19]. …”
Section: Discussionmentioning
confidence: 99%
“…In our previous study with different carbon nanoparticles, we have observed nanoparticles appearing on the bright field microphotographs as black dots, aggregated inside the cells or on the cell surface. 23 However, to determine the exact interaction of nanoparticles with the cell membrane, further studies need to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with the fact that dose is an important factor in the toxicity of carbon nanoparticles. 23,24 However, the toxic effects also depend on the type of cells, as it was observed that fibroblasts ( Figure 4) were less susceptible to HNC treatment than glioma cells. This might be explained by the high amount of HNC aggregates in fibroblast medium and lower affinity of the HNC particles to fibroblast cells, influencing adhesion to the cell membrane and probably HNC intake by cells.…”
Section: Discussionmentioning
confidence: 99%